Basalt-rhyolitic series of Galindez and Uruguay Islands (Antarctic Peninsula, Western Antarctica) as an object for geochemical modeling - Aleksieienko, A. G.; Shnyukov, S. E.; Lazareva, I. I.; Gavryliv, L. I. (Ukrainian Antarctic Journal, 2016)
This paper presents preliminary results of all stages of geochemical modeling of the evolution of the Galindez and Uruguay Islands (Antarctic Peninsula, West Antarctica) eruptive magmatism, characterizes the difficulties encountered and ways to overcome them. On the basis of the developed model the article attempts to assess the temperature, pressure and fluid modes of magmatic system during its evolution, as well as its ore-generating ability. The following was discovered: close conformity of the current magmatic system evolution to the accepted fractional crystallization model; temperature mode (-1130 ... 880 °С) and depth (9-12 km, lithostatic pressure 3-4 kbar) of magmatic chamber functioning; water content in initial and residual melts during all system evolution phases; mass fraction of liquid phase in system at the moment of fluid segregation (f = 0,27) and its temperature (T = 880 °С). However, the results should only be considered preliminary. The development of more accurate models requires a significant improvement of the initial geochemical data quality.